Markets Equilibrium: The Is-Lm Model - Frida Yanti Sirait; Mulyana Fitri; Isnaini Harahap (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
. The purpose of this study is to analyze how the concept of markets equilibrium: the IS-LM Model. This research uses library research method by using reference sources from books and journals according to the theme. The author uses a qualitative method which is explained graphically, namely the market balance of the IS-LM model where the focus is on money and goods markets associated with macroeconomics where researchers take the side of investors. The results of this study are that the balance in the economy is the point where the IS and LM curves intersect. This point provides an interest rate (r) and income level (Y) that satisfies the equilibrium conditions that occur in the goods market and money market. In other words, planned spending equals actual spending, and the demand for real money balances equals the supply. So that the IS-LM balance, it is stated that IS=LM.